(untitled) (Vietnam Journal of Community Medicine, 2022)
The descriptive, cross-sectional study was implemented in Innov Green Company from September, 2019 to December, 2019 using measurement tools to assess the situation of occupational safety and health conditions in this company. The results showed that the company had a council of labor protection and a labor safety and sanitation network. 7 out of 7 indicators of microclimate, dust, toxic gas, and organic solvents all met the permitted standards and 3/5 noise samples met the permitted standards.